(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
This note aims to offer an insightful reading about the decision of the european court of justice in case confédération paysanne v. Ministre de l’agriculture (c-528/16). It focuses on the reasons why the court extended the security measures provided by dir. Ce 2001/18 even to some new methods of mutagenesis; techniques used to make certain rape varieties herbicide-tolerant. In particular, this writing would highlight how the court used the precautionary principle to offer some a new guidance for the interpretation of this directive, such as for the other regulations related to the gmo discipline.